Comparing distance education and conventional education: observations from a comparative study of post-registration nurses - Tim Duffy; Iain Gilbert; David Kennedy; Poon Wai Kwong (Research in Learning Technology, 2002)
This retrospective study presents a comparison of assessment results achieved by distancelearning students and classroom-based students undertaking the same module in a degree course. The purpose of the comparison is to provide some objective measurement of the quality of distance education in relation to conventional classroom-based education. The authors have selected three groups of students, who have all undertaken the same module in the B. Sc Health Studies degree programme offered by the University of Paisley. One group (in Paisley) undertook their studies by means of conventional classroom-based education, the second (in Hong Kong) by supported distance learning with face-to-face contact in the form of tutorials, and the third (in a geographically dispersed group in the United Kingdom and other countries) by supported distance learning with no face-to-face contact. The results obtained by these three groups of students were analysed. Because of the differences in the size of the groups, the Kruskal- Wallis 1- Way Anova test was applied to validate the face value findings. The authors include findings from the literature comparing distance education with conventional education and from cross-cultural studies to present their data in context. Analysis of the assessment results showed that students from all three groups were successful in their studies, but the students studying by distance learning obtained significantly higher end-of-module results than their classroom-based colleagues. This latter finding reflects the conclusion that other investigators have reached In their discussion the authors identify educational, cultural and personal factors that may help to explain their findings. A limitation in the study is that it concerns only one module in the degree programme. The research now moves on to comparing students who have undertaken the whole degree programme by the means described